The Interplay Between Monocytes/Macrophages and CD4+ T Cell Subsets in Rheumatoid Arthritis - Roberts, Ceri A.; Dickinson, Abigail K.; Taams, Leonie S. (Frontiers in Immunology, 2015)
Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by inflammation of the synovial lining (synovitis). The inflammation in the RA joint is associated with and driven by immune cell infiltration, synovial hyperproliferation and excessive production of pro-inflammatory mediators, such as TNFα, IFNγ, IL-1β, IL-6 and IL-17, eventually resulting in damage to the cartilage and underlying bone. The RA joint harbors a wide range of immune cell types, including monocytes, macrophages and CD4+ T cells (both pro-inflammatory and regulatory). The interplay between CD14+ myeloid cells and CD4+ T cells can significantly influence CD4+ T cell function and conversely, effector vs. regulatory CD4+ T cell subsets can exert profound effects on monocyte/macrophage function. In this review, we will discuss how the interplay between CD4+ T cells and monocytes/macrophages may contribute to the immunopathology of RA.